A Numerical Solution for Heat Transfer in Nanofluid Flow Using Modified Lattice Boltzmann Method - Dini Faradina; Mohamad Subagus Fahmi; Dadan Purnama (International Journal of Applied Mathematics and Computing, 2024)
This research presents a numerical investigation into heat transfer in nanofluid flow using an advanced lattice Boltzmann method (LBM). The study modifies the standard LBM to incorporate the unique properties of nanofluids, such as enhanced thermal conductivity. We simulate convective heat transfer in a pipe with varying nanoparticle concentrations, assessing the effects on heat transfer rates. Results show that nanofluids significantly improve heat transfer efficiency, offering valuable insights for engineering applications in cooling systems.